Aircraft Propellers, an Outdated Innovation? - Alves, Pedro; Silvestre, Miguel; Gamboa, Pedro (KnE Engineering, 2020)
The race for speed ruled the early Jet Age on aviation. Aircraft manufacturers chased faster and faster planes in a fight for pride and capability. In the early 1970s, dreamed that the future would be supersonic, but fuel economy and not acceptable noise levels made that era never came. After the 1973 first oil crisis, the paradigm changed. The average cruise speed on newly developed aircraft started to decrease in exchange for improvements in many other performance parameters. At the same pace, the airliner’s powerplants are evolving to look more like a ducted turboprop, and less like a pure jet engine as the pursuit for the higher bypass ratios continues. However, since the birth of jet aircraft, the propeller-driven plane lost its dominant place in the market. Associated with the idea of going back to propeller-driven airplanes, and what it represented in terms of modernity and security, it started a propeller avoidance phenomenon on the travelers and thus on the airlines. Today, even with the modest research effort since the 1980s, the advanced propellers are getting closer efficiencies to the jet-powered engines at their contemporary typical cruise speeds. This paper gives a brief overview of the performance trends in aviation since the last century. Comparison examples between aircraft designed on different paradigms are presented. The use of propellers as a reborn propulsive device is discussed. Keywords: Propeller, Aircraft, Turboprop, Flight efficiency, Flight speed